Prevention of recurrent fetal growth retardation in patients with circulating antiphospholipid antibodies and genetic thrombophilia - E. A. Orudzhova; V. O. Bitsadze; M. V. Tretyakova; D. A. Doronicheva; F. Yakubova (Акушерство, гинекология и репродукция, 2022)
Aim: to evaluate the effectiveness of using low molecular weight heparin (LMWH) and low-dose acetylsalicylic acid (ASA) in preventing recurrence of early and late fetal growth retardation (FGR) in patients with antiphospholipid syndrome (APS) and/or genetic thrombophilia.Materials and Methods. A prospective randomized controlled study was conducted by examining 32 patients aged 23 to 43 years with a history of early and late II and III FGR as well as thrombophilia. Prevention protocol using LMWH and ASA was carried out from the pregravid period or early pregnancy. The control group included 35 women with uncomplicated pregnancy. Antiphospholipid antibodies (APA) were measured according to the Sydney antiphospholipid syndrome (APS) criteria by using enzyme immunoassay (ELISA): cardiolipin, β2-glycoprotein 1 and additionally antibodies to annexin V, prothrombin, etc. (IgG/IgM isotypes); lupus anticoagulant – by a three-stage method with Russell's viper venom; antithrombin III and protein C levels – by chromogenic method; prothrombin gene polymorphisms G20210A as well as factor V Leiden polymorphism – by chain reaction; homocysteine – by ELISA.Results. It was found that prevention protocol was effective in 78.1 % cases. FGR re-developed in 7 (21.9 %) pregnant women: in 2 (6.3 %) at 20 and 22 weeks, in 3 (9.4 %) at 30–32 weeks, in 2 (6.3 %) after 34 weeks of pregnancy. All these patients were found to have APA exceeding 40 U/ml with low dynamics of decline, 3 (9.4 %) were older than 35 years, 2 (6.3 %) had chronic kidney pathology and 1 (3.1 %) had a hypertension in the anamnesis.Conclusion. The use of LMWH and low-dose ASA starting from the pre-pregnancy period and early pregnancy as a part of complex therapy allows to effectively prevent re-development of FGR in patients with thrombophilia. In case of high APA titers, the use of LMWH and low-dose ASA may be ineffective, and alternative treatment methods in addition to anticoagulant therapy should be used to improve obstetric results.